Case report: Pulmonary synovial sarcoma in a long-term survivor of childhood Hodgkin lymphoma - Shilo, Konstantin; Kneuertz, Peter J.; Liebner, David; Chen, Wei (Frontiers in Oncology, 2023)
Solid organ malignancies have been reported in survivors of Hodgkin lymphoma treated with chemoradiation; however, to the best of our knowledge no cases of pulmonary synovial sarcoma have been documented in the literature in this cohort. We herein provide a detailed description of synovial sarcoma occurring in the lung of a long-term survivor of childhood Hodgkin lymphoma. A 29-year-old female never smoker with past medical history of Hodgkin lymphoma diagnosed at the age of 7 years and treated with chemotherapy and radiation therapy was admitted for management of pneumothorax. Wedge lung resection of an ulcerated subpleural nodule revealed a malignant spindle cell tumor that based on light microscopic and immunohistochemical features was classified as monophasic synovial sarcoma. The diagnosis was further confirmed by identification of SS18 (SYT) rearrangement by fluorescence in situ hybridization and SS18-SSX1 gene fusion by RNA sequencing. The case documents a rare occurrence of synovial sarcoma in a long-term survivor of childhood Hodgkin lymphoma. While comprising a typical genetic profile for synovial sarcoma, the tumor had unusual histological features such as cystic and low-grade morphology. The case suggests that synovial sarcoma falls within an expanding spectrum of secondary malignancies following prior treatment of Hodgkin lymphoma.